The effectiveness of low-dosed outpatient biopsychosocial interventions compared to active physical interventions on pain and disability in adults with nonspecific chronic low back pain: A protocol for a systematic review with meta-analysis. - Martin Hochheim; Philipp Ramm; Volker Amelung (PLoS ONE)
Background Best outpatient treatment of nonspecific chronic low back pain is high-dosed exercise that is maintained after therapy. Primary care biopsychosocial intervention (PCBI) is an outpatient multicomponent intervention that includes an active component (exercise, physical activity, or physiotherapy) and at least one psychological, social, or occupational component. Research has shown that PCBI can reduce pain intensity and disability. While scattered studies support low-dosed (<15 treatment hours) PCBI, there is no systematic review comparing the effectiveness of low-dosed PCBI treatment with traditional physical activity interventions in adults with nonspecific chronic low back pain (CLBP). Inclusion criteria Randomised controlled trials that evaluate low-dosed outpatient biopsychosocial interventions compared to physical treatment with an active component such as exercise, physical activity or usual physiotherapy treatment for adult participants (18 years or older) who suffer from nonspecific CLBP will be included. Methods A comprehensive search of multiple databases will be used to find relevant studies. The databases will be searched from inception to December 2021, with English or German language restrictions imposed. Keywords and derivatives of "chronic back pain", "exercise intervention", "cognitive-behavioral therapy", "primary care" and "randomized controlled trials" will be used. Sources will include CINAHL, Cochrane Central Register of Controlled Trials (CENTRAL), Ovid Medline, Physiotherapy Evidence Database (PEDro), PubMed and Web of Science. Discussion To our knowledge, this will be the first systematic review and meta-analysis of narrowly defined low- dosed PCBI across populations with nonspecific chronic low back pain. The objective of this review is to evaluate the effectiveness of low-dosed outpatient biopsychosocial interventions versus physical active interventions on pain intensity and disability in adults with CLBP. This study will provide evidence that could improve treatment options for patients with nonspecific CLBP. Trail registration Systematic review registration number: PROSPERO 2022 CRD42022302771. https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42022302771.